Physiological response of soybean (Glycine max L. Merrill) to foliar applied kaolin under irrigation in Sudan savanna of Nigeria - Madu, A I; Mohammed, I B; Sarkinfulani, M; Halima, M I (Journal of Current Opinion in Crop Science, 2023)
A field experiment was conducted during the hot, dry season of 2019 in the Sudan savanna of Nigeria to evaluate the effect of foliar-applied antitranspirant (kaolin) on growth, yield, and yield components of irrigated soybean [Glycine max (L.) Merrill]. Teaching and Research Farm of the Faculty of Agriculture Bayero University, Kano and Irrigation Research Station, Kadawa, Kano, under the Institute for Agricultural Research Ahmadu Bello University Zaria, Kaduna, represented the two locations. Treatments consisted of two varieties of soybean (TGX1835-10E and TGX1955-4F), three growth stages of foliar applied kaolin, and four application rates (0%, 3%, 6%, and 9% w/v %). The factors were laid out in a split-split-plot design and replicated three times. Varieties were allocated to main plots, growth stages of foliar-applied kaolin in subplots, and kaolin rates in sub-subplots. Cultural practices, soil physical and chemical analysis, and irrigation were conducted. Data collected from physiological parameters included intercepted photosynthetically active radiation, leaf chlorophyll content, stomatal conductance, and plant dry matter (g), were subjected to analysis of variance using Statistix-10 and significant means of treatments were separated using Tukey HSD at a 5% level of probability. The result revealed that variety and foliar applied kaolin at growth stages and its rates significantly affected the physiological parameters of irrigated soybeans. The highest physiological responses were recorded from TGX1955-4F and lower from the variety TGX1835-10E. Foliar applied kaolin at pod initiation, and kaolin rates of 3 and 6% indicated the highest effect on measured physiological parameters and grain yield.